Spatial Mismatch in Search Equilibrium - Coulson, N. Edward; Laing, Derek; Wang, Ping (Journal of Labor Economics, 2001)
We construct a search equilibrium model for a city with central and suburban labor markets that is consistent with the set of empirical regularities commonly associated with the spatial mismatch hypothesis: a higher rate of unemployment for central city residents than suburban residents, a higher job vacancy rate for suburban firms, and reverse commuting and higher suburban wages. The effectiveness and welfare implications of public policy programs that might be used to remedy the underlying mismatch are examined.